Integrated Management of Black Pod (Phytophthora palmivora) Disease of Cocoa Through Fungicides and Cultural Practices in Southwestern Ethiopia - Merga Jibat; Shamil Alo (International Journal on Food, Agriculture and Natural Resources, 2023)
Black pod disease of cocoa (Theobroma cacao L.) caused by Phytophthora palmivora is the major constraint in cocoa production in southwestern Ethiopia. Therefore, integrated field management trials were conducted to evaluate the efficacy of different fungicides against a disease epidemic of cocoa black pod in southwestern Ethiopia. The field experiment was laid out in a randomized complete block design with seven treatments and three replications. The experiment was performed during the 2021 and 2022 main cropping seasons using five fungicides: Copper oxychloride (Koka blue 50 WG) combined with cultural practices, Agro-laxyl 63.5 WP (Metalaxyl + Mancozeb) combined with cultural practices, Progress 250 EC (Propiconazole 25%) combined with cultural practices, Ethiozeb 80% WP (Mancozeb) combined with cultural practices, More 720 WP (Mancozeb  +Cymoxanil) combined with cultural practices, cultural practices alone and control without any cultural practices and fungicides spray for control of black pod infection. Cultural practices such as nutrient management, pruning, plant and field hygiene etc. were implemented in all treatments except control. The results of the experiment indicated that copper oxychloride (Koka blue 50 WG) combined with cultural practices significantly affected the cocoa black pod epidemics. When paired with cultural practices, copper oxychloride (Koka blue 50 WG) had a considerably greater impact on lowering disease severity (4.76) than the other treatments. Additionally, compared to control plots, the incidence of disease was reduced by more than 50% when cultural practices alone were used. This shows that in farms where black pod disease severity is low, the disease may be economically managed by implementing cultural measures alone. So, the the study's findings, black pod disease can be controlled in areas with a high disease incidence by combining the application of copper oxychloride (Koka blue 50 WG) with other cultural practices.